Is household income diversification welfare improving? The evidence from Philippine panel data. - Mendoza, Adrian R.
Using panel data from the Annual Poverty Indicator Surveys for 2007, 2008, and 2010, I estimate two-stage pooled and fixed effects models to examine the income diversification behavior of Filipino households, with a special emphasis on rural areas. In order to evaluate the welfare implications, I test for a significant effect of diversification on income and consumption volatility in the presence of idiosyncratic and aggregate shocks. The results support both risk aversion and wealth accumulation as valid motives for diversification, although the former is more dominant among poor and rural households. Owing to asset build-up, diversification helps well-off families mitigate future income and consumption fluctuations. However, there is no evidence of a similar effect for rural households whose diversification strategy is primarily subsistence-driven. This implies a situation where income diversification may further worsen unequal access to resources and opportunities.